Preparation method of lithium iron phosphate and lithium silicate composite material

After treatment or freezing and drying of the lithium iron phosphate battery through water, the wet metallurgical process is used to add specific chemical substances to the derived water water to form iron phosphate-SIO2 suspension liquid, and dry and wet grinding treatment. The composite material of lithium iron phosphate/lithium silicate has solved the problem of high acid -base raw materials in traditional methods and difficulty recycling waste batteries, and realized efficient use and good electrochemical properties.

CN119340532APending Publication Date: 2025-01-21SHANDONG HAIHUA GRP CO LTD +1

Patent Information

Application Number
CN202411291793.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

When preparing the cathode material of lithium iron phosphate battery, the traditional hydrometallurgy method uses a large amount of acid and alkali raw materials to cause high consumption and poor economic benefits, and it is difficult to achieve efficient recycling and recycling of used batteries.

Method used

Used lithium iron phosphate batteries are discharged, disassembled, and sorted, and then treated with water or freeze-dried to obtain waste lithium iron phosphate flakes. Hydrochloric acid and sodium hypochlorite are then added to deionized water, heated and stirred to generate iron phosphate-SiO2. The suspension is filtered and then added with sodium hydroxide and sodium carbonate to form a lithium carbonate suspension. After drying and wet grinding, it is finally roasted at high temperature in a protective atmosphere to obtain a lithium iron phosphate/lithium silicate composite material.

Benefits of technology

This method realizes the comprehensive comprehensive utilization of lithium iron phosphate batteries, reduces the use of acid -base raw materials, reduces production costs, improves the resource utilization rate, and has a better material for lithium iron phosphate/lithium silicate. Electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing a composite positive electrode material by using a waste battery, and belongs to the technical field of battery recovery. The method comprises the following steps: discharging, disassembling and sorting a waste lithium iron phosphate battery to obtain a positive plate, carrying out water treatment, separating from an aluminum foil to obtain a waste lithium iron phosphate sheet, adding sodium hypochlorite, tetraethoxysilane, deionized water and hydrochloric acid, stirring to obtain SiO2-coated iron phosphate precipitate particles and a lithium-containing solution, adding sodium hydroxide into the lithium-containing solution to adjust the pH value, and carrying out solid-liquid separation to obtain the lithium-ion battery cathode material. Adding sodium carbonate, heating and drying to obtain lithium carbonate precipitate. And adding a carbon source and alcohol into the SiO2-coated iron phosphate precipitate particles and lithium carbonate, carrying out ball milling, taking out, drying, and calcining in a protective atmosphere to obtain the positive electrode composite material. Compared with the prior art, according to the prepared positive electrode composite material, material particles contain a lithium silicate network, so that the specific discharge capacity of a battery material is effectively improved. The method is simple in process and suitable for comprehensive utilization of waste batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a lithium iron phosphate-lithium silicate composite material, belonging to the technical field of lithium ion batteries. Background Art

[0002] Portable electronics and electric vehicles, as well as the coming era of large-scale energy storage, will likely see the installed capacity of lithium-ion batteries exceed 6,500 GWh by 2050. Lithium iron phosphate batteries (LFP) are one of the most widely used cathode materials for lithium-ion batteries, accounting for half of the lithium-ion battery market. Due to the strong energy of Fe-O and PO bonds, the olivine crystal structure of LFP can be well maintained during repeated lithiation / delithiation cycles, giving LFP batteries a long cycle life and good high-temperature stability. The service life of LFP batteries is generally 5-8 years, and the next few years will be the climax of LFP battery retirement. A large amount of discarded lithium iron phosphate (SLFP) batteries will soon cause serious environmental and social problems. Therefore, it is urgent to develop a suitable SLFP battery recycling method.

[0003] A Chinese patent document with publication number CN113562717A discloses "a method for low-temperature recovery and regeneration of waste lithium iron phosphate batteries". In this method, waste lithium iron phosphate batteries are subjected to pretreatment such as discharge, disassembly, and separation to obtain lithium iron phosphate powder, the lithium iron phosphate powder is mixed with ammonium salt and then air-roasted at low temperature, and then leached with water to obtain lithium ion solution and iron phosphate, and then carbonate is added to the lithium ion solution to obtain precipitated lithium carbonate, and the lithium carbonate and iron phosphate are regenerated into lithium iron phosphate positive electrode material. This method uses an ammonium source and due to the limitation of its own olivine structure, lithium iron phosphate has a low ionic conductivity, resulting in its poor discharge specific capacity. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a lithium iron phosphate lithium silicate composite material, which overcomes the problem of high consumption of acid and alkali raw materials and poor economic benefits in the traditional hydrometallurgical method, and can simply and economically prepare lithium iron phosphate / lithium silicate positive electrode materials. The material obtained based on the present invention can be used again to make lithium iron phosphate batteries, realizing efficient utilization and recycling of waste lithium iron phosphate batteries. This method can realize the comprehensive utilization of waste lithium iron phosphate batteries, not only can the useful metal elements in the battery be recovered, but also other components of the battery can be reused, thereby improving resource utilization and reducing environmental pollution.

[0005] To achieve this object, the technical solution of the present invention is a method for preparing a lithium iron phosphate lithium silicate composite material, comprising the following steps: (1) After discharge, disassembly and sorting, waste lithium iron phosphate batteries are obtained to obtain positive electrode sheets, negative electrode sheets, separators, current collectors and metal casings; (2) treating the positive electrode sheet with water or freeze-drying to obtain waste lithium iron phosphate sheet and aluminum foil; (3) dissolving the waste lithium iron phosphate sheets in deionized water, adding hydrochloric acid to adjust the pH value to acidic, then adding sodium hypochlorite and ethyl orthosilicate, heating and stirring to obtain an iron phosphate-SiO2 suspension, filtering the iron phosphate-SiO2 suspension to obtain iron phosphate precipitate particles wrapped with SiO2 and a lithium-containing solution; (4) adding sodium hydroxide to the lithium-containing solution to adjust the pH value to alkaline, then adding sodium carbonate, heating to react to generate a lithium carbonate suspension, filtering and drying the lithium carbonate suspension to obtain a lithium carbonate precipitate; (5) mixing lithium carbonate precipitate, SiO2-coated iron phosphate precipitate particles, and carbon source, and then wet-grinding to obtain pretreated lithium iron phosphate regenerated material; (6) Under a protective atmosphere, the pretreated lithium iron phosphate recycled material is calcined at a high temperature to obtain a lithium iron phosphate / lithium silicate composite material.

[0006] Preferably, the water treatment in step (2) is an ultrasonic hydrothermal method or a hot and cold water alternating method.

[0007] Preferably, the ultrasonic hydrothermal method is to place the positive electrode sheet in a container filled with deionized water, then place the container in an ultrasonic cleaning machine, perform ultrasonic hydrothermal treatment on the positive electrode sheet, control the hydrothermal temperature to be 40-80°C, and after ultrasonic treatment for 0.5-2h, take out the positive electrode sheet, sort it, and obtain waste lithium iron phosphate sheet and aluminum foil.

[0008] Preferably, the hot and cold water alternating method is to place the positive electrode sheet alternately in hot water at 60-90°C and cold water at 10-30°C, repeating this process 3-5 times, and then taking out the positive electrode sheet and sorting it to obtain waste lithium iron phosphate sheet and aluminum foil.

[0009] Preferably, in step (2), the specific process of freeze-drying the positive electrode sheet is to place the positive electrode sheet in a freezing environment, set the temperature to -60 to -20°C, take it out after 0.5 to 10 hours, and then dry and sort the positive electrode sheet to obtain waste lithium iron phosphate sheets and aluminum foil.

[0010] Preferably, in step (3), the pH value is controlled at 1-3, the mass volume ratio of waste lithium iron phosphate sheet, sodium hypochlorite, ethyl orthosilicate and deionized water is 1g:0.4011-0.5395g:0.1648-0.3296g:20ml-150ml; the heating and stirring temperature is 20-40°C, the stirring speed is 200-400rpm / min, and the stirring time is 2-4h.

[0011] Preferably, in step (4), the pH value is controlled at 12-14, and the amount of sodium carbonate added is controlled to control the Li:CO32- The molar ratio is 2:0.99, the heating temperature is 90°C, and the heating time is 20~60min.

[0012] Preferably, in step (5), the carbon source is any one of glucose or sucrose or citric acid or starch; the molar ratio of the lithium carbonate to the iron phosphate precipitate particles wrapped with SiO2 is 1~1.1:1, and the amount of the carbon source added is 5%~20% of the sum of the mass of the lithium carbonate and the iron phosphate precipitate particles wrapped with SiO2.

[0013] Preferably, in step (6), the specific process of high temperature roasting is to first increase the roasting temperature to 250-400°C and keep it at that temperature for 1.5-3 hours; then increase the temperature to 650-800°C and keep it at that temperature for 5-8 hours.

[0014] The beneficial effects of the present invention are as follows: The traditional ultrasonic hydrothermal process uses external energy to reduce the adhesion between lithium iron phosphate and aluminum foil and induces separation, but it will induce side reactions and promote the formation of impurities. The technical solution of the present invention reduces the adhesion between waste lithium iron phosphate sheets and aluminum foil by freezing; compared with the traditional ultrasonic hydrothermal process, the waste lithium iron phosphate sheets and aluminum foil are separated by freezing separation, and the aluminum impurity content in the obtained waste lithium iron phosphate powder is low, and the electrochemical performance of the obtained lithium iron phosphate positive electrode material is better.

[0015] The technical solution of the present invention produces iron phosphate precipitation while tetraethyl orthosilicate is decomposed into silicon dioxide. At this time, silicon dioxide will be wrapped in the iron phosphate precipitation particles. SiO2 is wrapped in the precipitation particles to obtain the iron phosphate precipitation wrapped with SiO2. In the solid phase reaction of lithium carbonate and iron phosphate to synthesize lithium iron phosphate, lithium carbonate will react chemically with SiO2 inside the iron phosphate particles to generate lithium silicate, which enhances the ionic conductivity of lithium iron phosphate. Since the material particles contain a lithium silicate network, the discharge specific capacity of the battery material is effectively improved. Compared with directly adding silicon dioxide to the reaction system to prepare the iron phosphate precipitation wrapped with SiO2, the iron phosphate precipitation wrapped with SiO2 obtained by the technical solution of the present invention is more uniform, and a more uniform and stable lithium silicate network can be formed in the process of reacting with lithium carbonate later, and the obtained lithium iron phosphate / lithium silicate positive electrode material has better electrochemical performance.

[0016] The technical solution of the present invention can provide a comprehensive utilization approach for the recycling of waste batteries, does not use organic solvents for electrode separation, and realizes the green recycling of waste batteries while reducing waste liquid discharge. DETAILED DESCRIPTION

[0017] The present invention is further described below in conjunction with embodiments. Example 1

[0018] The waste lithium iron phosphate battery is completely discharged until the discharge voltage is zero, and then the positive electrode sheet, negative electrode sheet, separator, current collector and metal casing are obtained by disassembling and sorting; The positive electrode sheet is placed in a container filled with deionized water, and then the container is placed in an ultrasonic cleaning machine to perform ultrasonic hydrothermal treatment on the positive electrode sheet, and the hydrothermal temperature is controlled to be 60° C. After ultrasonic treatment for 1 hour, the positive electrode sheet is taken out and sorted to obtain waste lithium iron phosphate sheets and aluminum foil; Take 10g of waste lithium iron phosphate sheets, add 4.834g of sodium hypochlorite, 3.296g of ethyl orthosilicate, add 750ml of deionized water, add hydrochloric acid to adjust the pH to 2, stir at 30°C, stir at 300rpm / min, stir for 3h, and obtain 8.398g of iron phosphate precipitate particles wrapped with SiO2 and a lithium-containing solution; Sodium hydroxide was added to the lithium-containing solution to adjust the pH to 13, and sodium carbonate was added, and heated for 30 minutes to generate a lithium carbonate suspension. The lithium carbonate suspension was filtered and dried to obtain 2.345 g of lithium carbonate precipitate; Lithium carbonate and SiO2-wrapped iron phosphate are added to a ball mill at a molar ratio of 1.05:1, and then glucose is added, wherein the amount of glucose added is 10% of the sum of the mass of lithium carbonate and the SiO2-wrapped iron phosphate, to obtain a mixture; alcohol and zirconium oxide balls are then added, wherein the amount of alcohol added is twice the mass of the mixture, and the amount of zirconium oxide balls added is 20 times the mass of the mixture; the mixture is wet-milled at a speed of 500 rpm / min, and after 4 hours of wet-milling, the mixture is taken out and dried to obtain pretreated lithium iron phosphate regenerated material; The pretreated lithium iron phosphate regenerated material was placed in argon gas, first heated to 350°C and calcined for 2 hours, and then heated to 650°C and calcined for 6 hours to obtain a lithium iron phosphate / lithium silicate composite material, named 1# positive electrode material. Example 2

[0019] The waste lithium iron phosphate battery is completely discharged until the discharge voltage is zero, and then the positive electrode sheet, negative electrode sheet, separator, current collector and metal casing are obtained by disassembling and sorting; The positive electrode sheet is placed in a container filled with deionized water, and then the container is placed in an ultrasonic cleaning machine to perform ultrasonic hydrothermal treatment on the positive electrode sheet, and the hydrothermal temperature is controlled to be 40° C. After ultrasonic treatment for 2 hours, the positive electrode sheet is taken out and sorted to obtain waste lithium iron phosphate sheets and aluminum foil; Take 10g of waste lithium iron phosphate sheets, add 4.011g of sodium hypochlorite, 1.648g of ethyl orthosilicate, add 1500ml of deionized water, add hydrochloric acid to adjust the pH to 1, stir at 20°C, stir at 400rpm / min, stir for 4h, and obtain 7.916g of iron phosphate precipitate particles wrapped with SiO2 and a lithium-containing solution; Sodium hydroxide was added to the lithium-containing solution to adjust the pH to 12, and sodium carbonate was added, and heated for 60 minutes to generate a lithium carbonate suspension. The lithium carbonate suspension was filtered and dried to obtain 2.018 g of lithium carbonate precipitate; Lithium carbonate and SiO2-wrapped iron phosphate are added to a ball mill in a molar ratio of 1:1, and then glucose is added, wherein the amount of glucose added is 5% of the sum of the mass of lithium carbonate and the SiO2-wrapped iron phosphate, to obtain a mixture; alcohol and zirconium oxide balls are then added, wherein the amount of alcohol added is 5 times the mass of the mixture, and the amount of zirconium oxide balls added is 60 times the mass of the mixture; the mixture is wet-milled at a speed of 300 rpm / min, and after 8 hours of wet-milling, the mixture is taken out and dried to obtain pretreated lithium iron phosphate regenerated material; The pretreated lithium iron phosphate regenerated material was placed in argon gas, first heated to 250°C and calcined for 3 hours, and then heated to 650°C and calcined for 8 hours to obtain a lithium iron phosphate / lithium silicate composite material, named 2# positive electrode material. Example 3

[0020] The waste lithium iron phosphate battery is completely discharged until the discharge voltage is zero, and then the positive electrode sheet, negative electrode sheet, separator, current collector and metal casing are obtained by disassembling and sorting; The positive electrode sheet is placed in a container filled with deionized water, and then the container is placed in an ultrasonic cleaning machine to perform ultrasonic hydrothermal treatment on the positive electrode sheet, and the hydrothermal temperature is controlled to be 80° C. After ultrasonic treatment for 0.5 h, the positive electrode sheet is taken out and sorted to obtain waste lithium iron phosphate sheets and aluminum foil; Take 10g of waste lithium iron phosphate sheets, add 5.395g of sodium hypochlorite, 3.296g of ethyl orthosilicate, add 200ml of deionized water, add hydrochloric acid to adjust the pH to 3, stir at 40°C, stir at 200rpm / min, stir for 2h, and obtain 8.056g of iron phosphate precipitate particles wrapped with SiO2 and a lithium-containing solution; Sodium hydroxide was added to the lithium-containing solution to adjust the pH to 14, and sodium carbonate was added and heated for 20 minutes to generate a lithium carbonate suspension. The lithium carbonate suspension was filtered and dried to obtain 2.326 g of lithium carbonate precipitate; Lithium carbonate and SiO2-wrapped iron phosphate are added to a ball mill at a molar ratio of 1.1:1, and then sucrose is added, wherein the amount of glucose added is 20% of the sum of the mass of lithium carbonate and the SiO2-wrapped iron phosphate, to obtain a mixture; alcohol and zirconium oxide balls are then added, wherein the amount of alcohol added is 2 times the mass of the mixture, and the amount of zirconium oxide balls added is 10 times the mass of the mixture; the mixture is wet-milled at a speed of 700 rpm / min, and after wet-milling for 1 hour, the mixture is taken out and dried to obtain pretreated lithium iron phosphate regenerated material; The pretreated lithium iron phosphate regenerated material was placed in argon gas, first heated to 400°C and calcined for 1.5 hours, and then heated to 800°C and calcined for 5 hours to obtain a lithium iron phosphate / lithium silicate composite material, named 3# positive electrode material. Example 4

[0021] The waste lithium iron phosphate battery is completely discharged until the discharge voltage is zero, and then the positive electrode sheet, negative electrode sheet, separator, current collector and metal casing are obtained by disassembling and sorting; The positive electrode sheets were placed in hot water at 60°C and cold water at 10°C alternately for 5 times, and then the positive electrode sheets were taken out and sorted to obtain waste lithium iron phosphate sheets and aluminum foil; Take 10g of waste lithium iron phosphate sheets, add 4.834g of sodium hypochlorite, 3.296g of ethyl orthosilicate, add 750ml of deionized water, add hydrochloric acid to adjust the pH to 2, stir at 30°C, stir at 300rpm / min, stir for 3h, and obtain 8.299g of iron phosphate precipitate particles wrapped with SiO2 and a lithium-containing solution; Sodium hydroxide was added to the lithium-containing solution to adjust the pH to 13, and sodium carbonate was added, and heated for 30 minutes to generate a lithium carbonate suspension. The lithium carbonate suspension was filtered and dried to obtain 2.306 g of lithium carbonate precipitate; Lithium carbonate and SiO2-wrapped iron phosphate are added to a ball mill at a molar ratio of 1.05:1, and then glucose is added, wherein the amount of glucose added is 12% of the sum of the mass of lithium carbonate and the SiO2-wrapped iron phosphate, to obtain a mixture; alcohol and zirconium oxide balls are then added, wherein the amount of alcohol added is 2 times the mass of the mixture, and the amount of zirconium oxide balls added is 20 times the mass of the mixture; the mixture is wet-milled at a speed of 600 rpm / min, and after 3 hours of wet-milling, the mixture is taken out and dried to obtain pretreated lithium iron phosphate regenerated material; The pretreated lithium iron phosphate regenerated material was placed in argon gas, first heated to 350°C and calcined for 2.5 hours, and then heated to 650°C and calcined for 8 hours to obtain a lithium iron phosphate / lithium silicate composite material, named 4# positive electrode material. Example 5

[0022] The waste lithium iron phosphate battery is completely discharged until the discharge voltage is zero, and then the positive electrode sheet, negative electrode sheet, separator, current collector and metal casing are obtained by disassembling and sorting; The positive electrode sheets were placed in 90°C hot water and 30°C cold water alternately for 3 times, and then the positive electrode sheets were taken out and sorted to obtain waste lithium iron phosphate sheets and aluminum foil; Take 10g of waste lithium iron phosphate sheets, add 4.695g of sodium hypochlorite, 3.318g of ethyl orthosilicate, add 750ml of deionized water, add hydrochloric acid to adjust the pH to 2, stir at 30°C, stir at 300rpm / min, stir for 3h, and obtain 8.418g of iron phosphate precipitate particles wrapped with SiO2 and a lithium-containing solution; Sodium hydroxide was added to the lithium-containing solution to adjust the pH to 13, and sodium carbonate was added and heated for 30 minutes to generate a lithium carbonate suspension. The lithium carbonate suspension was filtered and dried to obtain 2.319 g of lithium carbonate precipitate; Lithium carbonate and SiO2-wrapped iron phosphate are added to a ball mill at a molar ratio of 1.02:1, and then glucose is added, wherein the amount of glucose added is 15% of the sum of the mass of lithium carbonate and the SiO2-wrapped iron phosphate, to obtain a mixture; alcohol and zirconium oxide balls are then added, wherein the amount of alcohol added is 2 times the mass of the mixture, and the amount of zirconium oxide balls added is 30 times the mass of the mixture; the mixture is wet-milled at a speed of 400 rpm / min, and after 5 hours of wet-milling, the mixture is taken out and dried to obtain pretreated lithium iron phosphate regenerated material; The pretreated lithium iron phosphate regenerated material was placed in argon gas, first heated to 400°C and calcined for 1.5 hours, and then heated to 700°C and calcined for 6 hours to obtain a lithium iron phosphate / lithium silicate composite material, named 5# positive electrode material. Example 6

[0023] The waste lithium iron phosphate battery is completely discharged until the discharge voltage is zero, and then the positive electrode sheet, negative electrode sheet, separator, current collector and metal casing are obtained by disassembling and sorting; The positive electrode sheet of the waste lithium iron phosphate battery is placed in a freezing environment, the temperature is set to -20°C, and the positive electrode sheet is taken out after being frozen for 10 hours, and then the positive electrode sheet is placed in a freeze dryer for drying to obtain a mixture of aluminum foil and waste lithium iron phosphate sheets, and the waste lithium iron phosphate sheets and aluminum foil are obtained by manual sorting; Take 10g of waste lithium iron phosphate sheets, add 4.695g of sodium hypochlorite, 3.318g of ethyl orthosilicate, add 750ml of deionized water, add hydrochloric acid to adjust the pH to 2, stir at 30°C, stir at 300rpm / min, stir for 3h, and obtain 8.458g of iron phosphate precipitate particles wrapped with SiO2 and a lithium-containing solution; Sodium hydroxide was added to the lithium-containing solution to adjust the pH to 13, and sodium carbonate was added, and heated for 30 minutes to generate a lithium carbonate suspension. The lithium carbonate suspension was filtered and dried to obtain 2.398 g of lithium carbonate precipitate; Lithium carbonate and SiO2-wrapped iron phosphate are added to a ball mill at a molar ratio of 1.02:1, and then glucose is added, wherein the amount of glucose added is 15% of the sum of the mass of lithium carbonate and the SiO2-wrapped iron phosphate, to obtain a mixture; alcohol and zirconium oxide balls are then added, wherein the amount of alcohol added is 2 times the mass of the mixture, and the amount of zirconium oxide balls added is 30 times the mass of the mixture; the mixture is wet-milled at a speed of 400 rpm / min, and after 5 hours of wet-milling, the mixture is taken out and dried to obtain pretreated lithium iron phosphate regenerated material; The pretreated lithium iron phosphate regenerated material was placed in argon gas, first heated to 400°C and calcined for 1.5 hours, and then heated to 700°C and calcined for 6 hours to obtain a lithium iron phosphate / lithium silicate composite material, named 6# positive electrode material. Example 7

[0024] The waste lithium iron phosphate battery is completely discharged until the discharge voltage is zero, and then the positive electrode sheet, negative electrode sheet, separator, current collector and metal casing are obtained by disassembling and sorting; The positive electrode sheet of the waste lithium iron phosphate battery is placed in a freezing environment, the temperature is set to -60°C, and the positive electrode sheet is taken out after freezing for 0.5 hours, and then the positive electrode sheet is placed in a freeze dryer for drying to obtain a mixture of aluminum foil and waste lithium iron phosphate sheets, and the waste lithium iron phosphate sheets and aluminum foil are obtained by manual sorting; Take 10g of waste lithium iron phosphate sheets, add 4.834g of sodium hypochlorite, 3.296g of ethyl orthosilicate, add 750ml of deionized water, add hydrochloric acid to adjust the pH to 2, stir at 30°C, stir at 300rpm / min, stir for 3h, and obtain 8.416g of iron phosphate precipitate particles wrapped with SiO2 and a lithium-containing solution; Sodium hydroxide was added to the lithium-containing solution to adjust the pH to 13, and sodium carbonate was added and heated for 30 minutes to generate a lithium carbonate suspension. The lithium carbonate suspension was filtered and dried to obtain 2.356 g of lithium carbonate precipitate; Lithium carbonate and SiO2-wrapped iron phosphate are added to a ball mill at a molar ratio of 1.05:1, and then glucose is added, wherein the amount of glucose added is 10% of the sum of the mass of lithium carbonate and the SiO2-wrapped iron phosphate, to obtain a mixture; alcohol and zirconium oxide balls are then added, wherein the amount of alcohol added is twice the mass of the mixture, and the amount of zirconium oxide balls added is 20 times the mass of the mixture; the mixture is wet-milled at a speed of 500 rpm / min, and after 4 hours of wet-milling, the mixture is taken out and dried to obtain pretreated lithium iron phosphate regenerated material; The pretreated lithium iron phosphate regenerated material was placed in argon gas, first heated to 350°C and calcined for 2 hours, and then heated to 650°C and calcined for 6 hours to obtain a lithium iron phosphate / lithium silicate composite material, named 7# positive electrode material. Comparative Example 1

[0025] The waste lithium iron phosphate battery is completely discharged until the discharge voltage is zero, and then the positive electrode sheet, negative electrode sheet, separator, current collector and metal casing are obtained by disassembling and sorting; The positive electrode sheet is placed in a container filled with deionized water, and then the container is placed in an ultrasonic cleaning machine to perform ultrasonic hydrothermal treatment on the positive electrode sheet, and the hydrothermal temperature is controlled to be 60° C. After ultrasonic treatment for 1 hour, the positive electrode sheet is taken out and sorted to obtain waste lithium iron phosphate sheets and aluminum foil; Take 10g of waste lithium iron phosphate sheets, add 4.834g of sodium hypochlorite, add 750ml of deionized water, add hydrochloric acid to adjust the pH to 2, stir at 30°C, stir at 300rpm / min, stir for 3h, and obtain 7.635g of iron phosphate precipitate particles wrapped with SiO2 and a lithium-containing solution; Sodium hydroxide was added to the lithium-containing solution to adjust the pH to 13, and sodium carbonate was added, and heated for 30 minutes to generate a lithium carbonate suspension. The lithium carbonate suspension was filtered and dried to obtain 2.345 g of lithium carbonate precipitate; Lithium carbonate and SiO2-wrapped iron phosphate are added to a ball mill at a molar ratio of 1.05:1, and then glucose is added, wherein the amount of glucose added is 10% of the sum of the mass of lithium carbonate and the SiO2-wrapped iron phosphate, to obtain a mixture; alcohol and zirconium oxide balls are then added, wherein the amount of alcohol added is twice the mass of the mixture, and the amount of zirconium oxide balls added is 20 times the mass of the mixture; the mixture is wet-milled at a speed of 500 rpm / min, and after 4 hours of wet-milling, the mixture is taken out and dried to obtain pretreated lithium iron phosphate regenerated material; The pretreated lithium iron phosphate regenerated material was placed in argon gas, first heated to 350°C and calcined for 2 hours, and then heated to 650°C and calcined for 6 hours to obtain lithium iron phosphate material, named 6# positive electrode material. Contrast agent 2

[0026] The waste lithium iron phosphate battery is completely discharged until the discharge voltage is zero, and then the positive electrode sheet, negative electrode sheet, separator, current collector and metal casing are obtained by disassembling and sorting; The positive electrode sheet is placed in a container filled with deionized water, and then the container is placed in an ultrasonic cleaning machine to perform ultrasonic hydrothermal treatment on the positive electrode sheet, and the hydrothermal temperature is controlled to be 60° C. After ultrasonic treatment for 1 hour, the positive electrode sheet is taken out and sorted to obtain waste lithium iron phosphate sheets and aluminum foil; Take 10g of waste lithium iron phosphate sheets, add 4.834g of sodium hypochlorite, 0.951g of silicon dioxide, add 750ml of deionized water, add hydrochloric acid to adjust the pH to 2, stir at 30°C, stir at 300rpm / min, stir for 3h, and obtain 8.398g of iron phosphate precipitate particles wrapped with SiO2 and a lithium-containing solution; Sodium hydroxide was added to the lithium-containing solution to adjust the pH to 13, and sodium carbonate was added, and heated for 30 minutes to generate a lithium carbonate suspension. The lithium carbonate suspension was filtered and dried to obtain 2.345 g of lithium carbonate precipitate; Lithium carbonate and SiO2-wrapped iron phosphate are added to a ball mill at a molar ratio of 1.05:1, and then glucose is added, wherein the amount of glucose added is 10% of the sum of the mass of lithium carbonate and the SiO2-wrapped iron phosphate, to obtain a mixture; alcohol and zirconium oxide balls are then added, wherein the amount of alcohol added is twice the mass of the mixture, and the amount of zirconium oxide balls added is 20 times the mass of the mixture; the mixture is wet-milled at a speed of 500 rpm / min, and after 4 hours of wet-milling, the mixture is taken out and dried to obtain pretreated lithium iron phosphate regenerated material; The pretreated lithium iron phosphate regenerated material was placed in argon gas, first heated to 350°C and calcined for 2 hours, and then heated to 650°C and calcined for 6 hours to obtain a lithium iron phosphate / lithium silicate composite material, named 7# positive electrode material. Test Example 1

[0027] The lithium iron phosphate positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-2 are made into button batteries, specifically including the following steps: According to the mass ratio of 8:1:1, the regenerated positive electrode composite material, binder powder (PVDF), and conductive agent powder (SuperP) are weighed respectively, and evenly ground and mixed. Add the binder powder solvent (NMP), grind the mixed powder into a uniform slurry, the slurry solid content is 58%, and apply it on the non-smooth surface of the aluminum foil so that the positive electrode coating and the aluminum foil are tightly bonded. Place the coated aluminum foil in a vacuum drying oven at 60°C for 6h to remove NMP. Check whether the dried pole piece has powdering and cracking, and place the pole piece with good appearance on the punching machine for slicing, and make the positive pole piece dry for standby use. The lithium sheet is used as the counter electrode of the regenerated positive electrode, 1 mol / L LiPF6 / EC:DMC (1:1) is used as the electrolyte in the button battery, and the Celgard2325 composite film is used as the battery separator. The assembled button battery parts are placed on the battery sealing machine mold for compression packaging, then removed from the glove box and placed horizontally for 6-12 hours to allow the electrolyte to fully penetrate the inside of the battery. The battery is then tested and analyzed for various electrochemical properties in the Xinwei constant temperature test system.

[0028]

[0029] It can be seen from Table 1 that the electrochemical performance of the positive electrode material obtained in Examples 1 to 7 is better than that of the positive electrode material obtained in Comparative Examples 1-2. This is because the present invention adopts a coprecipitation method, and while tetraethyl orthosilicate is decomposed into silicon dioxide, iron phosphate precipitation is produced. At this time, silicon dioxide will be wrapped in iron phosphate precipitation particles. SiO2 is wrapped in precipitation particles to obtain iron phosphate precipitation wrapped with SiO2. In the solid phase reaction of lithium carbonate and iron phosphate to synthesize lithium iron phosphate, lithium carbonate will react chemically with SiO2 inside the iron phosphate particles to generate lithium silicate, which enhances the ionic conductivity of lithium iron phosphate. Since the material particles contain a lithium silicate network, the discharge specific capacity of the battery material is effectively improved. Compared with directly adding silicon dioxide, the iron phosphate precipitation wrapped with SiO2 obtained by the present invention is more uniform, and a more uniform and stable lithium silicate network can be formed in the process of reacting with lithium carbonate later. The obtained lithium iron phosphate / lithium silicate positive electrode material has good electrochemical performance. The electrochemical performance of the positive electrode material obtained in Examples 6-7 is slightly better than that of the positive electrode material obtained in Comparative Examples 1-5. This is because the traditional ultrasonic hydrothermal process uses external energy to reduce the bonding force between lithium iron phosphate and aluminum foil, induces separation, but induces side reactions and promotes the formation of impurities. The technical solution of the present invention reduces the bonding force between waste lithium iron phosphate sheets and aluminum foil by freezing; compared with the traditional ultrasonic hydrothermal process, the waste lithium iron phosphate sheets and aluminum foil are separated by freezing separation, and the aluminum impurity content in the obtained waste lithium iron phosphate powder is low, and the electrochemical performance of the obtained lithium iron phosphate positive electrode material is better. At the same time, the present invention can provide a comprehensive utilization method for the recycling of waste batteries, without using organic solvents for pole piece separation, while reducing waste liquid discharge, realizing the green recycling of waste batteries.

Claims

1. A method for preparing a lithium iron phosphate-lithium silicate composite material, characterized in that: The steps include: (1) After discharge, disassembly and sorting, waste lithium iron phosphate batteries are obtained to obtain positive electrode sheets, negative electrode sheets, separators, current collectors and metal casings; (2) treating the positive electrode sheet with water or freeze-drying to obtain waste lithium iron phosphate sheet and aluminum foil; (3) dissolving the waste lithium iron phosphate sheets in deionized water, adding hydrochloric acid to adjust the pH value to acidic, then adding sodium hypochlorite and ethyl orthosilicate, heating and stirring to obtain an iron phosphate-SiO2 suspension, filtering the iron phosphate-SiO2 suspension to obtain iron phosphate precipitate particles wrapped with SiO2 and a lithium-containing solution; (4) adding sodium hydroxide to the lithium-containing solution to adjust the pH value to alkaline, then adding sodium carbonate, heating to react to generate a lithium carbonate suspension, filtering and drying the lithium carbonate suspension to obtain a lithium carbonate precipitate; (5) mixing lithium carbonate precipitate, SiO2-coated iron phosphate precipitate particles, and carbon source, and then wet-grinding to obtain pretreated lithium iron phosphate regenerated material; (6) Under a protective atmosphere, the pretreated lithium iron phosphate recycled material is calcined at a high temperature to obtain a lithium iron phosphate / lithium silicate composite material.

2. The method for preparing the lithium iron phosphate lithium silicate composite material according to claim 1, characterized in that: The water treatment in step (2) is an ultrasonic hydrothermal method or a hot and cold water alternating method.

3. The method for preparing the lithium iron phosphate lithium silicate composite material according to claim 2, characterized in that: The ultrasonic hydrothermal method comprises the following steps: placing the positive electrode sheet in a container containing deionized water, placing the container in an ultrasonic cleaning machine, performing ultrasonic hydrothermal treatment on the positive electrode sheet, controlling the hydrothermal temperature to be 40-80° C., and after ultrasonic treatment for 0.5-2 hours, taking out the positive electrode sheet, sorting it, and obtaining waste lithium iron phosphate sheet and aluminum foil.

4. The method for preparing the lithium iron phosphate / lithium silicate composite material according to claim 2, characterized in that: The hot and cold water alternating method comprises the following steps: placing the positive electrode sheet alternately in hot water at 60-90° C. and cold water at 10-30° C., repeating for 3-5 times, taking out the positive electrode sheet, sorting it, and obtaining waste lithium iron phosphate sheet and aluminum foil.

5. The method for preparing the lithium iron phosphate lithium silicate composite material according to claim 1, characterized in that: In the step (2), the positive electrode sheet is freeze-dried. The method comprises the following steps: placing the positive electrode sheet in a freezing environment, setting the temperature at -60 to -20°C, taking it out after 0.5 to 10 hours, and then drying and sorting the positive electrode sheet to obtain waste lithium iron phosphate sheets and aluminum foil.

6. The method for preparing the lithium iron phosphate lithium silicate composite material according to claim 1, characterized in that: In the step (3), the pH value is controlled at 1-3, the mass volume ratio of waste lithium iron phosphate sheet, sodium hypochlorite, ethyl orthosilicate and deionized water is 1g:0.4011-0.5395g:0.1648-0.3296g:20ml-150ml; the heating and stirring temperature is 20-40°C, the stirring speed is 200-400rpm / min, and the stirring time is 2-4h.

7. The method for preparing the lithium iron phosphate lithium silicate composite material according to claim 1, characterized in that: In the step (4), the pH value is controlled at 12-14, and the amount of sodium carbonate added is to control the Li:CO3 content in the lithium-containing solution. 2- The molar ratio is 2:0.99; the heating temperature is 90°C and the heating time is 20~60min.

8. The method for preparing the lithium iron phosphate lithium silicate composite material according to claim 1, characterized in that: In the step (5), the carbon source is any one of glucose, sucrose, citric acid or starch; the molar ratio of the lithium carbonate to the iron phosphate precipitate particles wrapped with SiO2 is 1-1.1:1, and the amount of the carbon source added is 5%-20% of the sum of the mass of the lithium carbonate and the iron phosphate precipitate particles wrapped with SiO2.

9. The method for preparing the lithium iron phosphate lithium silicate composite material according to claim 1, characterized in that: In the step (6), the specific process of high temperature roasting is to first increase the roasting temperature to 250-400°C and keep it at that temperature for 1.5-3 hours; then increase the temperature to 650-800°C and keep it at that temperature for 5-8 hours.

Citation Information

Patent Citations

  • Method for recycling waste lithium iron phosphate battery at low temperature regenerating lithium iron phosphate positive electrode material

    CN113562717A

Cited By

  • Separation and recovery method of positive electrode material of waste lithium iron phosphate battery

    CN121005412A

  • Modified lithium-sulfur silicate composite lithium-supplementing type lithium iron phosphate positive electrode material and preparation method thereof

    CN122117878A

  • Modified lithium silicate-sulfur composite lithium supplement type lithium iron phosphate cathode material and preparation method thereof

    CN122117878B

  • Method for modifying and repairing waste lithium iron phosphate positive electrode material by using tetrabutyl silicate and application of method in deep sea field

    CN122315124A

  • Method for repairing waste lithium iron phosphate positive electrode material by modifying with tetrabutyl silicate and application in deep sea field

    CN122315124B